Spectrophotometric Determination of Hydrazine - Deepa, B.; Balasubramanian, N.; Nagaraja, K.S. (Asian Journal of Chemistry, 2016)
A spectrophotometric method for the determination of hydrazine, which involves conversion of hydrazine to ammonium sulphate by Zn/H2SO4 reductor column, has been developed. The formed ammonium sulphate is determined based on Berthelot reaction using salicylic acid, sodium hypochlorite and sodium nitroprusside. The lmax for the formed dye is at 648 nm and the calculated molar absorptivity is 1.8 × 104 L mol–1 cm–1. The methos is useful for determining hydrazine in the concentration range 0.25–2.5 ppm with the relative standard deviation of 2% for n = 10 at 1.5 ppm of hydrazine. Response of the proposed method for hydrazine determination in the presence of potential interferents is evaluated. The proposed method has been successfully applied for the estimation of hydrazine in feed waters for high-pressure steam generating boilers. The results obtained in the developed method compare well with the p-dimethylamino-benzaldehyde (p-DAB) method and by recovery studies of added hydrazine.